2018
DOI: 10.3389/fimmu.2018.00527
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to Tumor Angiogenesis From Innate Immune Cells Within the Tumor Microenvironment: Implications for Immunotherapy

Abstract: The critical role of angiogenesis in promoting tumor growth and metastasis is strongly established. However, tumors show considerable variation in angiogenic characteristics and in their sensitivity to antiangiogenic therapy. Tumor angiogenesis involves not only cancer cells but also various tumor-associated leukocytes (TALs) and stromal cells. TALs produce chemokines, cytokines, proteases, structural proteins, and microvescicles. Vascular endothelial growth factor (VEGF) and inflammatory chemokines are not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
336
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 323 publications
(342 citation statements)
references
References 261 publications
(290 reference statements)
2
336
1
3
Order By: Relevance
“…The cells are capable of recognizing and killing cancer cells without a requirement for antigen exposure (Baek et al, 2018). NK cells have antitumor ability in an immature state, while differentiated NK cells acquire PD-1 receptor that is expressed at a considerable rate upon tumor progression (Albini, Bruno, Noonan, & Mortara, 2018). There are two phenotypes for NK cells: canonical and adoptive.…”
Section: Nk Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells are capable of recognizing and killing cancer cells without a requirement for antigen exposure (Baek et al, 2018). NK cells have antitumor ability in an immature state, while differentiated NK cells acquire PD-1 receptor that is expressed at a considerable rate upon tumor progression (Albini, Bruno, Noonan, & Mortara, 2018). There are two phenotypes for NK cells: canonical and adoptive.…”
Section: Nk Cellsmentioning
confidence: 99%
“…STAT3 also promotes cancer cell survival (Kesanakurti, Chetty, Dinh, Gujrati, & Rao, 2013). In addition, STAT3 is a stimulator of tumor angiogenesis (Albini et al, 2018). Signaling pathways directed by STAT has been clarified in Figure 3.…”
Section: Statmentioning
confidence: 99%
“…Immunohistochemistry analysis showed a clear rebalance (i.e., an increment) of M1/M2 polarization ratio in C51 FL Rnaset2-injected mice, concomitant with inhibition of MDSCs, granulocytes and vessel numbers. The myeloid cell compartment appears to be a crucial determinant in the fate of tumor growth [27], indeed M2-like macrophages and/or TAMs as well as MDSCs associate with worse tumor clinical outcome, tumor dissemination, angiogenesis, immunosuppression, and metastasis [21,35,36]. Concerning tumor angiogenesis, it has been reported that several derivative peptides from human RNASET2 protein structure can exert antiangiogenic effects using HUVEC tube formation assay and using ex vivo CAM assay, and this effect is dependent on the peptide's ability to bind actin [37].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the high expression of granzyme B and FasL in cytotoxic cells of the tumor microenvironment was obviously observed in the combination-treated mice (Figure 5d). [22] Compared to PLG-CA4 alone, the CD31-positive signals were further reduced, and the intertumor microvessels were poorly structured after treatment with PI3Kγ inhibitor (Figure 5e). The critical role of tumorinfiltrating macrophages in promoting tumor angiogenesis is strongly established.…”
Section: Mechanisms Of Antitumor Performance By Attenuating Immunosupmentioning
confidence: 97%